Synthesis and immunological evaluation of protein conjugates of Neisseria meningitidis X capsular polysaccharide fragments - Morelli, Laura; Cancogni, Damiano; Tontini, Marta; Nilo, Alberto; Filippini, Sara; Costantino, Paolo; Romano, Maria Rosaria; Berti, Francesco; Adamo, Roberto; Lay, Luigi (Beilstein Journal of Organic Chemistry, 2014)
A vaccine to prevent infections from the emerging Neisseria meningitidis X (MenX) is becoming an urgent issue. Recently MenX capsular polysaccharide (CPS) fragments conjugated to CRM197 as carrier protein have been confirmed at preclinical stage as promising candidates for vaccine development. However, more insights about the minimal epitope required for the immunological activity of MenX CPS are needed. We report herein the chemical conjugation of fully synthetic MenX CPS oligomers (monomer, dimer, and trimer) to CRM197. Moreover, improvements in some crucial steps leading to the synthesis of MenX CPS fragments are described. Following immunization with the obtained neoglycoconjugates, the conjugated trimer was demonstrated as the minimal fragment possessing immunogenic activity, even though significantly lower than a pentadecamer obtained from the native polymer and conjugated to the same protein. This finding suggests that oligomers longer than three repeating units are possibly needed to mimic the activity of the native polysaccharide.
Keywords: carbohydrates; glycoconjugates; immunology; multivalent glycosystems Neisseria meningitidis; vaccines